Redescriptions of five species of marine peritrichs, Zoothamnium plumula, Zoothamnium nii, Zoothamnium wang, Pseudovorticella bidulphiae, and Pseudovorticella marina (Protista, Ciliophora) - Ji, Daode; Shin, Mann Kyoon; Choi, Joong Ki; Clamp, John C.; Al-Rasheid, Khaled A. S. (Zootaxa, 2011)
The significant similarity of congeners and an accumulation of inaccurate descriptions or misinterpretations in previous studies can make it difficult to separate species of peritrich ciliates from one another. Isolates collected from Chinese coastal waters allowed investigation and redescription of three marine species of peritrichs, Zoothamnium plumula Kahl, 1933, Z. nii Ji et al., 2005 and Z. wangi Ji et al., 2005, emphasizing in particular details of characters observed in vivo, infraciliature and comparisons with morphologically similar congeners. Brief redescriptions based on new material also are provided for two other marine peritrichs, Pseudovorticella bidulphiae (Stiller, 1939) Ji et al., 2009 and P. marina (Greeff, 1870) Ji et al., 2009.